PENGEMBANGAN MEDIA PEMBELAJARAN ELEKTRONIK BERBASIS MIND MAPPING PADA TEMA INDAHNYA KEBERAGAMAN DI NEGERIKU KELAS IV SD NEGERI 2 PACOR - Zumrotus Sholihah Fahrudin; Titi Anjani; Riawan Yudi Purwoko (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
Learning media is a tools that made in a structured way to convey information and interact with the audience. Mind mapping media is a creative way of thoughts on each subject to record what is learned. The development of learning media are developed in a modern way. The media that will be develop is mind mapping based electronic learning media. The research aims to: (1) determine the development procedure. (2) Knowing the feasibility of mind mapping learning media. Mind mapping media uses the ADDIE research method. The steps for the ADDIE method are as follows: analysis, design, development, implementation, and evaluation. The results of the research are (1) to produce mind mapping based electronic learning media products. (2) The results of the feasibility by media experts get an average score of 3.8 and were declared very practical and material experts with 3.1 of total average score, were declared practical. (3) The practicality of mind mapping based on electronic learning media is taken from student responses with small, medium and operational scale trials with an average score of each subject 3.6, 3.71, and 3.75 which means it’s very practical.